PLGA microsphere/PVA hydrogel coatings suppress the foreign body reaction for 6 months - Gu, Bing (J Control Release, 2018)
The application of dexamethasone releasing poly (lactic-co-glycolic acid) (PLGA) microspheres embedded in a poly vinyl alcohol (PVA) hydrogel coatings have been successfully used in the suppression of the foreign body response (FBR) to implantable glucose sensors. In the current study, dexamethasone- loaded PLGA microspheres were prepared by blending two types of PLGA polymers (RG503H and DLG7E with MW of ca. 25 kDa and 113 kDa, respectively) to achieve long-term (6 months) inhibition of the FBR. The microsphere composition was optimized according to the in vitro drug release profiles. Microspheres with DLG7E/RG503H/dexamethasone=70/13.3/16.7 weight % composition, when embedded in a PVA hydrogel, provided a continuous drug release for 6 months. By combining the aforementioned microspheres with microspheres composed solely of the DLG7E polymer within a similar PVA hydrogel realized an even longer (greater than 7 months) in vitro drug release. A heat map was constructed to depict the daily in vitro drug released and elucidate possible lag phases that could affect the pharmacodynamic response. These drug-loaded implant coatings were investigated in vivo (rat model) and showed inhibition of the foreign body response for 6 months. These results suggest that the minimum effective daily dose to counter chronic inflammation is ca. 0.1 µg per mg of coating surrounding a 0.5×0.5×5 mm silicon implant (dummy sensor). Accordingly, these drug-eluting composite coatings can ensure long-term inflammation control for miniaturized implantable devices.